2020
DOI: 10.36899/japs.2020.1.0010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioaerosols in Controlled Environment Broiler Houses at Different Stages of Growth

Abstract: Poultry is critical in fulfilling the protein requirements of the growing populations across the world. However, concerns about the public and environmental health impacts of bioaerosols emissions from intensive poultry facilities are increasing. In the present study, characterization of bioaerosols from air and litter samples was carried out using both culture and non-culture based methods (Flow cytometry). Eighteen controlled environment broiler houses (with approximate 27000 birds) were investigated and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Overall, the essential biochemical characteristics of Salmonella spp. in this study were similar to those of other reports [20,21].…”
Section: Discussionsupporting
confidence: 94%
“…Overall, the essential biochemical characteristics of Salmonella spp. in this study were similar to those of other reports [20,21].…”
Section: Discussionsupporting
confidence: 94%
“…In some recent reports, Dai et al found that Staphylococcus, Faecalibacterium, Ruminococcus, Corynebacterium, and Blautia accounted for a large proportion in the analysis of the microbial community of the chicken house [1], whereas Wu et al reported that Jeotgalicoccus, Facklamia, Psychrobacter, Brachybacterium, and Brevibacterium accounted for dominance [12]. Although the results of the dominant taxa were not completely consistent, several related studies have shown that the bacterial community structure in broiler houses is determined by environmental factors and is considerably different from that in the atmosphere [13,35]. Our results on significant differences in airborne bacteria revealed that the variation in bacterial characteristics is large and random in atmospheric environments without human intervention, whereas changes in the abundance, diversity, composition, and structure of bacteria in a broiler house environment are mainly affected by artificial controls.…”
Section: Discussionmentioning
confidence: 96%
“…Some differential media are also selective, for instance, MacConkey agar, which is selective for Gram-negative coliforms and can also differentiate between lactose-fermenting and non-lactose-fermenting bacteria (Ahmed et al 2016 ; Nigro and Steward 2015 ). Such traditional microbiological culture-based approaches have been followed recently for indoor bioaerosol characterisation (Yasmeen et al 2020 ; and Nasir et al 2018 ).…”
Section: Aerosols and Bioaerosolsmentioning
confidence: 99%